Political turnover and corporate financialization: Evidence from China - Lyu, Simeng; Qi, Yong; Yang, Shuo; Dong, Shaoyu (Frontiers in Psychology, 2022)
This paper examines the effect of political turnover on corporate financialization by using data of listed companies and top prefecture level officials in China between 2007 and 2020. We find that the turnover of mayors significantly decreases corporate financialization, while the turnover of party secretaries has no impact on corporate financialization. Moreover, these results are moderated by the characteristics of government officials and firm’s characteristics. Our results further show that changes by mayors increase fixed asset investment and decrease cash holdings, and, thus, reduce corporate financialization. These findings could assist in solving the “from real to virtual” problems, strengthening financial services, and realizing high-quality economic development.